Financial transactions in Islamic banking are viable alternatives to the conventional banking transactions - Jalil, Md Abdul; Rahman, Muhammad Khalilur (Centre for Promoting Ideas, USA, 2010)
Islam has prohibited riba (interest) on loan given. When a lender lends money to another person, he is allowed to get back the capital amount only and not any additional amount which is usually fixed interest on the capital. Taking interest on loan given caused cruelty and injustice to poor people in the society during prophet Muhammad’s time who were unable to pay back the capital and the interest. So, Prophet Muhammad encouraged the rich people to give qard al-hasan (interest free loan) to the poor and needy people to help them to solve their problems. That’s why Allah (the Creator) prohibited taking interest but encouraged people who have money to invest the money in business. The profit obtained from business is permitted (halal) but fixed rate interest taken on loan given to a person is riba (interest) and it is prohibited. As Allah (the Creator) has prohibited interest, Muslims are prohibited to give interest, to take interest and to write down the interest transaction. Hence, Muslim scholars have invented some Islamic transactions which do not involve interest and Islamic banks are adopting these Islamic transactions. The objective of this paper is to narrate and analyze the Islamic banking transactions which are interest free and they are considered as alternatives to the conventional banking transactions.